The influence of cross-linguistic similarities on L2 idiom production - Masoomeh Yeganehjoo,; Yap, Ngee Thai; Mardziah Hayati Abdullah,; Tan, Bee Hoon (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Some idiomatic expressions are associated with concepts that are deeply interlaced in L1 and L2 cultures. This property motivates investigation of cross-linguistic similarities which could affect the storage, representation and production of L2 idioms. In a priming experiment, the response latencies of 27 competent Iranian learners of English were measured to determine how cross-linguistic similarities at both the conceptual and lexical levels can influence the production of English idiomatic expressions. The participants were exposed to auditory primes in Persian that share some degree of similarity between the L2 idiom and its L1 idiom counterpart. The study found that the Persian prime that is the shared lexical item in both the L1 and L2 idioms and the idiom key for the L1 idiom exhibited the shortest reaction time for the production of the L2 idiom. The Persian prime that was the shared concept for both the L1 and L2 idioms did not facilitate the production of the L2 idiom. It recorded the longest reaction time and statistical analysis showed no significant difference in the reaction time with the control condition which used Persian primes that were semantically and phonologically unrelated to both the L1 and L2 idioms. The results of this study suggest that the related primes that were concrete lexical units make a greater contribution in the recall of the L2 idiomatic expressions compared to the abstract shared figurative meaning.